Structure and Conductivity Correlation in NASICON Based Na3Al2P3O12 Glass: Effect of Na2SO4 - Mandal, Indrajeet; Chakraborty, Saswata; Ghosh, Manasi; Dey, Krishna K.; Annapurna, K.; Allu, Amarnath R. (Frontiers in Materials, 2022)
Identifying the factors influencing the movement of sodium cations (Na+) in glasses accelerates the possible options of glass-based solid electrolyte materials for their applications as a promising electrolyte material in sodium-ion batteries. Nevertheless, due to the poor correlation between the structure and conductivity in glass materials identifying the factors governing the conductivity still exist as a challenging task. Herein, we have been investigated the DC-conductivity variations by correlating the structure and conductivity in sodium superionic conductor (NASICON) based Na3Al2P3O12 (NAP) glass (mol%: 37.5 P2O5 – 25.0 Al2O3 – 37.5 Na2O) due to the successive substitution of Na2SO4 for Al2O3. Structural variations have been identified using the Raman and magic-angle spinning nuclear magnetic resonance (MAS-NMR) (for 31P, 23Na, and 27Al nuclei) and conductivity measurements have been done using the impedance spectroscopy. From the ac-conductivity spectra, the correlations between mean square displacement (MSD) and dc-conductivity and between the Na+ concentration and dc-conductivity have also been evaluated. Raman spectra reveal that the increase in the Na2SO4 concentration increases the number of isolated SO42- sulfate groups that are charge compensated by the Na+ cations in the NAP glass. MAS-NMR spectra reveal that the increase in Na2SO4 concentration increases the concentration of non-bridging oxygens and further neither S-O-P nor S-O-Al bonds are formed. Impedance spectroscopy reveals that, at 373 K, the DC conductivity of the NAP glass increases with increasing the Na2SO4 up to 7.5 mol% and then decreases with the further increase. In the present study, we have shown that the mobility of sodium cations played a significant role in enhancing the ionic-conductivity. Further, we have shown that inter-ionic coulombic interactions and the structural modification with the formation of SO42- units significantly influence the critical hopping length of the sodium cations and consequently the mobility and the ionic conductivity. The present study clearly indicates that, based on the compositions, glass materials can also be treated as strong-electrolyte materials.